The effects of exergames for cognitive function in older adults with mild cognitive impairment: a systematic review and metaanalysis - Cai, Xiaowan; Xu, Liya; Zhang, Hanyue; Sun, Tingting; Yu, Jingjing; Jia, Xiao; Hou, Xiao; Sun, Ruizhe; Pang, Jian (Frontiers in Neurology, 2024)
Purpose Exergames are an innovative method that can promote neuroplasticity and improve the cognitive abilities of the elderly. This study aimed to compare the effects of single-task and multi-task exergames on the cognitive ability of the elderly with mild cognitive impairment (MCI). Methods Computerized literature search was performed using PubMed, Web of Science, EBSCO, Elsevier, ProQuest, China National Knowledge Infrastructure (CNKI), Wanfang and VIP database to identify relevant articles from the establishment of the database from inception to April 1, 2024. The inclusion criteria were: (i) participants aged 60 or older diagnosed with mild cognitive impairment, regardless of gender; (ii) use of randomized controlled trials (RCTs); (iii) interventions involving exergames with physical activity or as the primary variable; and (iv) outcome measures using standardized neuropsychological instruments to assess cognitive function, including statistical data on sample size, mean, and standard deviation. Finally, the included study comprised a total of 526 participants. Mean difference (MD) and 95% confidence interval (CI) were used to synthesize the effect size in the data. Results 11 studies were included. Due to the differences in the intervention methods, subgroup analysis was performed on the included research. Compared with the control group assessed by the Montreal Cognitive Assessment Scale, the single-task intervention improved the cognitive ability of the elderly with MCI (MD 3.40, 95% CI 2.43–4.37), the Mini-Mental State Examination Scale (MD 2.38, 95% CI −2.03 to 2.72), the Trail Making Test (MD −3.89, 95% CI −6.45 to −1.33), and the Digit Span Forward test (MD 1.16, 95% CI 0.73–1.60). Conclusion This meta-analysis supports that exergames could be an effective cognitive rehabilitation method for MCI patients. Our study recommends that patients implement a customized exergames program and adhere to it for a long time. It is necessary to pay attention to the exercise guidelines and provide evidence from clinicians. Strengths and limitations of this study (1) This meta-analysis supports that exergames could be an effective cognitive rehabilitation method for MCI patients. Our study recommends that patients implement a customized exergames program and adhere to it for a long time. It is necessary to pay attention to the exercise guidelines and provide evidence from clinicians. (2) This research provides preliminary evidence for the clinical utility of VR tasks developed for mild cognitive impairment. (3) In this paper, only relevant studies in Chinese and English were searched, and no studies in other languages were searched.